Analisis Intervensi Foot Massage Pada Lansia Immobility Dengan Gangguan Mobilitas Fisik: Intervensi Foot Massage Pada Lansia Immobility - Rini Anggreani; Eny Sutria; Rasdiyanah (Nursing Practice Journal, 2025)
Disorders of physical mobility are characterized by a decrease in muscle strength and range of motion, which is a problem in the muscles and joints. Provision of early mobilization to physical mobility disorders through foot massage. Based on the events in the field of early mobilization in post-stroke patients, it has not received attention. Lack of physical activity after stroke can inhibit the range of joint motion, so that if this continues to occur, it will cause total dependence. One form of initial rehabilitation in stroke patients is to provide mobilization in the form of a passive foot massage and active exercises. That very early mobilization is one of the key factors in patient care. Foot massage has an effect on muscles and joints and reduces pain, and makes the body more relaxed. This research is a case study conducted on one elderly patient who experiences problems with physical mobility. After giving interventions to the elderly, Mr. MN found that the foot massage intervention increases muscle strength and provides a comfortable and relaxed effect on patients during the intervention lasting for 3 days. Thus, this foot massage therapy can be applied to increase the mobility of the elderly.